Why and how do general practitioners teach? An exploration of the motivations and experiences of rural Australian general practitioner supervisors. Issue 1 (December 2015) - Ingham, Gerard; Fry, Jennifer; O'Meara, Peter; Tourle, Vianne
Abstract Background In medical education, a learner-centred approach is recommended. There is also a trend towards workplace-based learning outside of the hospital setting. In Australia, this has resulted in an increased need for General Practitioner (GP) supervisors who are receptive to using adult learning principles in their teaching. Little is known about what motivates Australian GP supervisors and how they currently teach. Methods A qualitative study involving semi-structured interviews with 20 rural GP supervisors who work within one Regional Training Provider region in Australia explored their reasons for being a supervisor and how they performed their role. Data was analysed using a thematic analysis approach. Results GP supervisors identified both personal and professional benefits in being a supervisor, as well as some benefits for their practice. Supervision fulfilled a perceived broader responsibility to the profession and community, though they felt it had little impact on rural retention of doctors. While financial issues did not provide significant motivation to teach, the increasing financial inequity compared with providing direct patient care might impact negatively on the decision to be or to remain a supervisor in the future. The principal challenge for supervisors was finding time for teaching. Despite this, there was little evidence of supervisors adopting strategies to reduce teaching load. Teaching methods were reported in the majority to be case-based with styles extending from didactic to coach/facilitator. The two-way collegiate relationship with a registrar was valued, with supervisors taking an interest in the registrars beyond their development as a clinician. Conclusion Supervisors report positively on their teaching and mentoring roles. Recruitment strategies that highlight the personal and professional benefits that supervision offers are needed. Practices need assistance to adopt models of supervision and teaching that will help supervisors productively manage the increasing number of learners in their practices. Educational institutions should facilitate the development and maintenance of supportive supervision and a learning culture within teaching practices. Given the variety of teaching approaches, evaluation of in-practice teaching is recommended.